Du bon usage de la vieillesse - Gaëlle Magder (Genre, Sexualité et Société)
Gaëlle Magder had conducted a photographic work offering a different view of old age. Refusing to seeing negative images of the body altered in situations of dependency or abandonment, she chose the view of a very positive, cheerful and optimistic that goes against the grain of the commonplace. It also noted that self-representation and management of advanced age are not foreign to the logic of class.